2015
DOI: 10.3906/vet-1502-57
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the retinol-binding protein 4 gene (RBP4) and its association with carcass and meat quality traits in swine

Abstract: To investigate the influence of the retinol-binding protein 4 gene (RBP4) on the carcass and meat quality traits of swine, polymorphism was observed by PCR-SSCP in four Chinese native pig breeds (Huoshouhei, Anqingliubai, Wannanhei, and Wei), that were carefully selected for economic traits. The results revealed one SNP (A>G) of the RBP4 gene in these breeds, excluding Huoshouhei. The AA genotype was the predominant genotype and allele A was the predominant allele with higher frequencies. A further analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The most significant QTL accounted for over 50% of phenotypic variation. Among the 18 genes annotated in the QTL regions involved in growth or metabolic function, the igf1 and tgf ‐ β receptors have been reported to be significantly associated with FCR in chickens 106,107 . If these candidate markers can prove powerful for phenotypic evaluation in future breeding programmes, this approach will significantly increase the efficiency of carp production.…”
Section: Genetic Basis Of Economically Important Traitsmentioning
confidence: 99%
“…The most significant QTL accounted for over 50% of phenotypic variation. Among the 18 genes annotated in the QTL regions involved in growth or metabolic function, the igf1 and tgf ‐ β receptors have been reported to be significantly associated with FCR in chickens 106,107 . If these candidate markers can prove powerful for phenotypic evaluation in future breeding programmes, this approach will significantly increase the efficiency of carp production.…”
Section: Genetic Basis Of Economically Important Traitsmentioning
confidence: 99%
“…The Wannan Black pig is a typical Chinese indigenous, disease-resistant breed with high fertility, and a crude-feed tolerance that has been bred in the south of Anhui province by artificial selection for a long time. Our previous study about retinol-binding protein 4 (RBP4) gene and cholesteryl estertransfer protein (CETP) gene in Wannan black pig revealed that RBP4 was significantly associated with average back-fat thickness and meat color b* value, and identified a mutation in CETP, which had significant effects on the expression in liver and correlated positively with serum lipid and meat fat phenotypes [17,18]. Moreover, other genes and microRNAs related with immune traits and fertility have been identified [19,20].…”
Section: Introductionmentioning
confidence: 99%